Pemanfaatan Digital Marketing Dalam Meningkatkan Pengembangan UMKM di Desa Kebondalem, Kecamatan Bareng, Kabupaten Jombang - Dimas Oktorio Fadilla; Indah Respati Kusumasari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The era of the industrial revolution 4.0 and currently moving towards 5.0, forces all parties to improve to keep up with the pace of industrial development. Marketing is now evolving into a more modern form of digital marketing. The implementation method used by the East Java UPN Veterans KKN-T Group 3 in carrying out this activity was the door to door method. The use of digital marketing has several advantages, including targets that can be set according to demographics, domiciles, lifestyles, and even habits. Quick results are visible so that marketers can take corrective action or change if something is deemed inappropriate.